Pemberdayaan Masyarakat dengan Pembuatan Ekoenzim Berbasis Rumah Tangga di Desa Lajut - Immy Suci Rohyani; Nada Anjani; Intan Permata Sari; Baiq Dea Nisrina Atika; Nur Yani Wulandari (Jurnal Pengabdian Magister Pendidikan IPA, 2022)
Waste is a big problem that we often encounter in everyday life, one of which is in the village of Lajut District Praya Central Lombok Regency. Lack of public awareness and unavailability of hygiene facilities and infrastructure, such as laystall (TPS), waste cans and waste transport trucks in Lajut Village is a significant problem to be solved. This community empowerment activity aims to increase the understanding of the community in Lajut Village, especially housewives about the use of household-based fruit and vegetable waste into ecoenzyme. Ecoenzyme is the result of processing fruit, flower or vegetable waste that undergoes fermentation process with the help of sugar (molasses). Socialization is carried out by direct counseling and mentoring methods to the participant community. Community empowerment program with the manufacture of household-based ecoenzyme is declared on target because of the active role and response of the community in the process of making ecoenzyme. Thus in the future it is expected that waste in Lajut Village can be reduced by processing waste produced by the community into something useful, one of which is ecoenzyme.